Sun Exposure over a Lifetime in Australian Adults from Latitudinally Diverse Regions. (19th February 2013) - Lucas, Robyn M.; Valery, Patricia; van der, Ingrid; Dwyer, Terence; Pender, Michael P.; Taylor, Bruce; Ponsonby, Anne‐Louise; ,
Abstract Spatio‐temporal patterns in sun exposure underlie variations in skin cancer incidence and vitamin D deficiency, indicate effectiveness of sun protection programs and provide insights into future health risks. From 558 adults across four regions of Australia (Brisbane (27°S), Newcastle (33°S), Geelong and the Western Districts of Victoria (37°S) and Tasmania (43°S)), we collected: self‐report data on time‐in‐the‐sun from age 6 years; natural skin color and ethnicity; silicone skin casts (for cumulative skin damage); and serum for vitamin D status. Ambient ultraviolet radiation (UVR) at the location of residence, with time‐in‐the‐sun, was used to calculate a "UVR dose" for each year of life. Individuals maintained their ranking compared to their peers for time‐in‐the‐sun in summer compared to winter and across ages (Spearman rho 0.24–0.84, all P < 0.001). Time‐in‐the‐sun decreased with age in all birth cohorts, and over calendar time. Summer time‐in‐the‐sun increased with increasing latitude (P < 0.001). Seasonal variation in vitamin D status had greater amplitude and vitamin D deficiency increased with increasing latitude. Temporal patterns are consistent with effectiveness of sun protection programs. Higher relative time‐in‐the‐sun persists from childhood through adulthood. Lower summer time‐in‐the‐sun in the warmest location may have implications for predictions of UVR‐related health risks of climate change.